Kinetics Model of Cananga (Cananga Odorata) Fresh Flower Extraction using Microwave Hydrodistillation Method - Darnengsih, Darnengsih; Ni’mah, Hikmatun; Mahfud, Mahfud; Kartika Fitri, Ayu Chandra (UI Scholars Hub, 2024)
Recent studies have focused on improving essential oil extraction methods by incorporating advanced technologies, such as microwave-assisted hydrodistillation (MHD). Despite these advancements, further research is necessary to fully understand how different kinetic models influence extraction efficiency. This study evaluates several kinetic models for extracting essential oil from fresh Cananga flowers using MHD, examining how varying microwave power affects extraction rates and correlates with kinetic model parameters. The extraction process involved introducing 200 grams of fresh Cananga flowers in 400 mL of distilled water and subjecting the mixture to microwave power levels of 200 W, 400 W, and 600 W. The extraction lasted for 180 minutes, with measurements periodically 20 minutes. The data ob-tained analysed using first-order, second-order, power law, hyperbolic kinetic models, and the Elovich’s equation. Re-sults showed that the hyperbolic and power law models provided the best fit for the extraction data, with high accuracy demonstrated by a strong correlation (R² = 0.9992) and low root mean square error (RMSE = 0.0042). These findings suggest that these kinetic models are highly effective for describing the MHD extraction of Cananga essential oil, offer-ing insights for optimizing the process.